2022
DOI: 10.3390/ma15030887
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Texture on the Structural Adhesive Joining Properties of Aluminum 7075 and TEPEX®

Abstract: In the process of continuous improvement of manufacturing processes, this study was developed within the framework of the Ecovoss project, based on the inclusion of lightweight and new materials parts in the automotive sector. The objective was based on the replacement of aluminum welding operations with the option of adhesive operations with other types of materials such as polyamides or, in this case, a TEPEX® composite material (Dynalite 202-c200/50% TYP 13). The aim of this work is to test the best texturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A particularly significant share of adhesive joints is observed in the automotive industry [ 9 , 10 , 11 ]. These joints are used in numerous applications in the manufacturing stage of cars, vans, trucks and buses (urban two axle, articulated and tourist buses).…”
Section: Introductionmentioning
confidence: 99%
“…A particularly significant share of adhesive joints is observed in the automotive industry [ 9 , 10 , 11 ]. These joints are used in numerous applications in the manufacturing stage of cars, vans, trucks and buses (urban two axle, articulated and tourist buses).…”
Section: Introductionmentioning
confidence: 99%
“…The friction characteristics of the surface can be effectively improved by machining the texture with regular geometric dimensions and an orderly arrangement on the part surface. Surface modification has been widely used in many fields; for example, in the field of material surface friction reduction [2][3][4] and friction pair surface wear resistance [5,6], on some special occasions where surface friction needs to be increased [7], in environments where the system needs to reduce vibration [8][9][10], in the special field of resistance to adhesion [11], in the special environment of anti-creep [12], with long-term low-temperature equipment [13], and when the equipment needs to increase the bearing capacity [14], in the field of maintaining wettability [15], as well as areas with functional hydrophobicity requirements [16] and scenarios with increased adhesion [17]. It has shown good application prospects and become an effective way to achieve the high efficiency, miniaturization and high reliability of mechanical equipment [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the research it was found that the Ni-P/Si 3 N 4 layers produced in the bath with the Si 3 N 4 nanoparticle content in the amount of 2 g/dm 3 are more resistant to wear and show greater adhesion than the Ni-P/Si 3 N 4 layers deposited in the bath with 5 g/dm 3 of the dispersion phase. The same AW-7075 aluminum alloy was one of the materials examined by Pereira et al [45], who tried to replace aluminum welding operations with adhesive operations of other types of materials, such as polyamides (TEPEX ® -Dynalite 202-c200/50% TYP 13, Composite manufactured by LANXESS Deutschland GmbH from Koln, Germany). The Authors concentrated on texturing of substrate made in 7075 aluminum specimens for structural adhesion with TEPEX by AF-163-2 film.…”
mentioning
confidence: 99%